2014
DOI: 10.1097/pec.0000000000000106
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Team Size and Task Performance in Pediatric Trauma Resuscitation

Abstract: Resuscitation task completion varies by team size, with a nonlinear association between number of team members and completed tasks. Management of team size during high-acuity activations, those without prior notification, and those in which the patient has a penetrating injury may help optimize performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 25 publications
0
22
0
1
Order By: Relevance
“…A further eight studies were identified by checking the references lists. Among these 165 studies, 50 were eligible according to the inclusion criteria (online supplementary table S1),4 5 8 13 21–66 and five of these evaluated the impact of video review in regards to improvement in patient care (PICOS)8 21 23 41 62 (figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A further eight studies were identified by checking the references lists. Among these 165 studies, 50 were eligible according to the inclusion criteria (online supplementary table S1),4 5 8 13 21–66 and five of these evaluated the impact of video review in regards to improvement in patient care (PICOS)8 21 23 41 62 (figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…There were 6 cohort or case–control studies,8 21–23 27 42 27 cross-sectional studies24 25 28 30 33–40 43 44 46 47 49 51–54 56–59 65 66 and 17 case reports or series4 5 13 26 27 29 31 32 45 48 50 55 60–64 (figure 2). There were no trials or protocols of RCTs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…14 In paediatric trauma the optimal team size is suggested to be seven persons with effectiveness decreasing with more team members. 15 Nonetheless, the optimal size of a cardiac arrest team is currently unknown.…”
Section: Discussionmentioning
confidence: 99%